Sex and Age Composition of Walrus Groups Hauled Out on Ice Floes in the Bering and Chukchi Seas, 2013-2015 ... - Chadwick V Jay; L.T. Quakenbush; J. Citta; Anthony S Fischbach; Brian Battaile (U.S. Geological Survey, 2020)
These data are in one table with age and sex composition counts of groups of walruses on ice floes in the northern Bering and Chukchi Seas. Counts were collected by visual observations from boats. ...